Unravelling the biological secrets of microchimerism by single-cell analysis. (28th September 2017) - Ståhlberg, Anders; El-Heliebi, Amin; Sedlmayr, Peter; Kroneis, Thomas
Abstract: The presence of microchimeric cells is known for >100 years and well documented since decades. Earlier, microchimeric cells were mainly used for cell-based non-invasive prenatal diagnostics during early pregnancy. Microchimeric cells are also present beyond delivery and are associated to various autoimmune diseases, tissue repair, cancer and immune tolerance. All these findings were based on low complexity studies and occasionally accompanied by artefacts not allowing the biological functions of microchimerism to be determined. However, with the recent developments in single-cell analysis, new means to identify and characterize microchimeric cells are available. Cell labelling techniques in combination with single-cell analysis provide a new toolbox to decipher the biology of microchimeric cells at molecular and cellular level. In this review, we discuss how recent developments in single-cell analysis can be applied to determine the role and function of microchimeric cells.